ผลของการฝึกออกกำลังกล้ามเนื้อต้นขาด้วยวิธีการอย่างง่าย ในผู้ป่วยข้อเข่าเสื่อม - ชฎิล สมรภูมิ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
To evaluate the effects of quadriceps strengthening exercise with modified regimen in patients with mild to moderate primary knee osteoarthritis. Forty two subjects, mean ages 61 years, with diagnosed as mild to moderate primary knee osteoarthritis were studied. Randomized single blind clinical trial was conducted to compared between supervised quadriceps strengthening exercise with modified regimen, progressive resistive exercise using quadriceps board and anklets and home program free weight isotonic exercise. Quadriceps strength was measured by isokinetic machine. Knee pain and functional abilities of knee joints were measured by modified WOMAC scale every week until the end of the forth week. The results showed no statistically significant difference between two groups in quadriceps strength (right side p = 0.917, left side p = 0.667), in knee pain, (right side p =0.381, left side p =0.406) and in functional abilities (right side p=0.692, left side p=0.816). The comparison between before exercise and each week of quadriceps strength, knee pain and functional abilities showed significant increment of quadriceps strength at the end of the second week (p<0.01), decrement of knee pain and improvement of functional abilities showed significant at the end of the first week (p<0.01) of both groups. In conclusion, this study show that quadriceps strengthening exercise training in patients with mild to mederate primary knee osteoarthritis will decrease knee pain, increase functional ability since the end of the first week and increase quadriceps strength since the end of the second week. There is no significant difference of quadriceps strength, knee pain and functional ability between supervised quadriceps strengthening exercise with modified regimen and home program exercise in patients with mild to moderate primary knee osteoarthritis.